Corrigendum to "The SESAME/CASSE instrument listening to the MUPUS PEN insertion phase on comet 67P/Churyumov–Gerasimenko" [Acta Astronaut., DOI: 10.1016/j.actaastro.2016.02.018]. (June 2016) - Knapmeyer, M.; Fischer, H.-H.; Knollenberg, J.; Seidensticker, K.J.; Thiel, K.; Arnold, W.; Schmidt, W.; Faber, C.; Finke, F.; Möhlmann, D.
Abstract: This contribution corrects a table given in a previous contribution.